2022
DOI: 10.1093/hr/uhac147
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated fine-tuning of miRNA expression in tetraploid potato

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs, which modulate the abundance and spatiotemporal accumulation of target mRNAs at transcriptional and post-transcriptional levels and through that play important roles in several biological processes in plants. Here we show that in polyploid species, CRISPR/Cas9 system can be used for fine-tuning of miRNA expression, which can have broader range of applications compared to knock-out mutants. We established the complete pipeline for CRISPR-Cas9-mediated modulation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Increased effectiveness of introducing targeted mutations and likelihood of tetra-allelic mutations More complex constructs. More potential off-targets Andersson et al 2017 , Kusano et al 2018 , Carlsen et al 2022 , Lukan et al 2022 Testing plant RNA promoter/-s Arabidopsis U6 promoter ( AtU6 ) Effective and universal for dicotyledonous plants Less effective than native potato promoters Kusano et al 2018 , Banfalvi et al 2020 , Gonzales et al 2021 , Perroud et al 2022 Using geminivirus replicons (GVRs) Elements from the bean yellow dwarf virus (BeYDV) Improved frequency of HR-generated mutations No clear evidence that the GVR-based CRISPR/Cas vectors are more effective in potato than those containing the standard T-DNA backbone Butler et al 2015 , Butler et al 2016 Optimizing CRISPR/Cas delivery method Agrobacterium -mediated stable transformation Possible generation of tetra-allelic mutants. Possible induction of large fragment deletions/insertions Frequently occurring mosaic effects and somaclonal variations in edited plant tissues.…”
Section: Applications Of Crispr/cas In Potatomentioning
confidence: 99%
See 4 more Smart Citations
“…Increased effectiveness of introducing targeted mutations and likelihood of tetra-allelic mutations More complex constructs. More potential off-targets Andersson et al 2017 , Kusano et al 2018 , Carlsen et al 2022 , Lukan et al 2022 Testing plant RNA promoter/-s Arabidopsis U6 promoter ( AtU6 ) Effective and universal for dicotyledonous plants Less effective than native potato promoters Kusano et al 2018 , Banfalvi et al 2020 , Gonzales et al 2021 , Perroud et al 2022 Using geminivirus replicons (GVRs) Elements from the bean yellow dwarf virus (BeYDV) Improved frequency of HR-generated mutations No clear evidence that the GVR-based CRISPR/Cas vectors are more effective in potato than those containing the standard T-DNA backbone Butler et al 2015 , Butler et al 2016 Optimizing CRISPR/Cas delivery method Agrobacterium -mediated stable transformation Possible generation of tetra-allelic mutants. Possible induction of large fragment deletions/insertions Frequently occurring mosaic effects and somaclonal variations in edited plant tissues.…”
Section: Applications Of Crispr/cas In Potatomentioning
confidence: 99%
“…More than 25% of plants regenerated after stable Agrobacterium -mediated transformation showed the presence of four allelic mutations in the GBSS , whereas the editing effectivity was significantly lower (less than 10% of full allelic mutants) when the vector variants with only two sgRNAs and/or without the dMac3 were used (Kusano et al 2018 ). In the most recently published study, Lukan et al ( 2022 ) demonstrated the effectiveness of using CRISPR/Cas9 to modulate miRNA expression in two potato cultivars, Désirée and Rywal, through the use of dual sgRNA constructs designed for targeting both 5ʹ and 3ʹ ends of three selected MIR genes (Lukan et al 2022 ).…”
Section: Applications Of Crispr/cas In Potatomentioning
confidence: 99%
See 3 more Smart Citations